Ilusão e realidade em Ivaporunduva: a televisão na cultura quilombola. Análise a partir da Folkmídia - Almeida, Eliane de Souza (2005)
This study of case focus, from a fild research, biography and opened interviewa observe how a television, as a mass cominication mean, transform or influence the culture of maroon comunity. The object of this analisys is the maroon comunity from Ivaporunduva, in Eldorado Paulista, a country city, in Vale do Ribeira region. Their way of life has been constantly treatned by the intention of the barrage construction on the Ribeira do Iguape river s border, in which are several maroons comunity, and also Ivaporunduva, due to lack of public politics that keep their rights, and also the lack of job, what brings the young out of the comunity in order to fetch new horizons. T.V. is part of a new universe in the maroon reality and it enters in those men and women s life from the country as a entertainment vehicle and a door to the ilusion world and realities where they go for it and many times they get frustrated. The maroon culture and its transformations after television arrived in Ivaporunduva will be analysed from the Folkmidia, a theoric space that analyses the way in which the comunication means get elements from the popular culture and vice-versa. And it is the vice-versa that minds us.